URGENSI LINGKUNGAN PESANTREN DALAM MEMBENTUK AKHLAK SANTRI DI PP. AL-ANWAR PACULGOWANG DIWEK JOMBANG - Lutfi Ardianto (MA'ALIM: Jurnal Pendidikan Islam, 2021)
The environment can be engineered by creating a positive climate in the environment, where this engineering supports the formation of a person's character. The purpose of this study was to determine the urgency of the pesantren environment in shaping the morals of the students at Al-Anwar Islamic Boarding School Paculgowang Diwek Jombang. This study used a qualitative approach with a case study type. The data collection techniques using observation, interviews, and documentation. Data taken in the form of interviews, events, reports and documents. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data is by constructing some data so that it produces the same data. The results of this study indicate that, the urgency of the pesantren environment in shaping the morals of the students at the Al-Anwar Paculgowang Islamic Boarding School is by: instilling values through the study of moral books, through the management of the boarding school, implementing the habituation of activities and the rules of the boarding school. As for the formation of morals, namely by exemplary, creating a positive climate in supporting morals and morals such as book recitation, congregational prayer, ro, an, mujahadah and istighosah. Supporting factors in the formation of morals are the attention of the management, implementation of boarding rules, the figure of the board and senior santri as role models. The inhibiting factors are the one-meter holiday and the Eid al-Fitr and the lack of people who exemplify and dare to prevent evil.